Pearls and Pitfalls of Phrenic Nerve Transfer for Shoulder Reconstruction in Brachial Plexus Injury - Doi, Kazuteru; Sem, Sei Haw; Ghanghurde, Bipin; Hattori, Yasunori; Sakamoto, Sotetsu (Journal of Brachial Plexus and Peripheral Nerve Injury, 2021)
Objectives The purpose of this study was to report the functional outcomes of phrenic nerve transfer (PNT) to suprascapular nerve (SSN) for shoulder reconstruction in brachial plexus injury (BPI) patients with total and C5–8 palsies, and its pulmonary complications.Methods Forty-four out of 127 BPI patients with total and C5–8 palsies who underwent PNT to SSN for shoulder reconstruction were evaluated for functional outcomes in comparison with other types of nerve transfers. Their pulmonary function was analyzed using vital capacity in the percentage of predicted value and Hugh-Jones (HJ) breathless classification. The predisposing factors to develop pulmonary complications in those patients were examined as well.Results PNT to SSN provided a better shoulder range of motion significantly as compared with nerve transfer from C5 root and contralateral C7. The results between PNT and spinal accessory nerve transfer to SSN were comparable in all directions of shoulder motions. There were no significant respiratory symptoms in majority of the patients including six patients who were classified into grade 2 HJ breathlessness grading. Two predisposing factors for poorer pulmonary performance were identified, which were age and body mass index, with cut-off values of younger than 32 years old and less than 23, respectively.Conclusions PNT to SSN can be a reliable reconstructive procedure in restoration of shoulder function in BPI patients with total or C5–8 palsy. The postoperative pulmonary complications can be prevented with vigilant patient selection.
Keywords: brachial plexus injury; phrenic nerve transfer; suprascapular nerve